Elucidating intracellular trafficking of His-rich peptide coacervates - Liu, Yiting (Nanyang Technological University, 2024)
Inspired by the Humboldt squid beak proteins, self-coacervating peptides are being developed as novel drug delivery systems. These pH-responsive, histidine-rich peptides exhibit exceptional coacervate-forming abilities, enabling them to efficiently recruit and release a diverse range of therapeutic cargos. Their capabilities align with current trends in pharmaceutic developments, but to progress towards clinical applications, a comprehensive understanding of the mechanism underlying their intracellular trafficking is pivotal for precise control over their delivery capabilities. In this study, fluorescence-labelled endocytic markers were employed to track the journey of these peptide coacervates within cells. HeLa cells were successfully transfected with plasmids encoding four fluorescence-labelled endocytic markers, Rab5, Rab7, early endosome autoantigen 1 (EEA1), and lysosomal associated membrane protein 1 (LAMP1). Two modifications of the peptide coacervate, GW31 and GW36, were optimised for colocalization studies. Enhanced green fluorescence protein and dyes were used as coacervate cargos and the coacervates formed were introduced to the endosome marker-expressing cells to screen for colocalization. The samples were observed at different timepoints to capture different stages of coacervate trafficking. Using fluorescence and confocal microscopy techniques, we were able to identify colocalization of coacervates with endocytic compartments labelled by Rab5, EEA1, and LAMP1 respectively, at 30 - 90 min after coacervate addition. Rab5 and EEA1 are well-established early endosome markers and was seen interacting with coacervates across multiple timepoints. LAMP1 is indicative of cell lysosomes, and interaction with coacervates were prominent at all timepoints after coacervate had entered cells. Late endosome marker, Rab7, did not show colocalization with coacervates. Overall, these results significantly enhanced our understanding of coacervate behaviour within cellular environments, providing crucial insights that can allow better control of coacervate uptake and release for future drug delivery systems. To improve on the current study, future works can focus on exploring more endocytic markers and conducting live cell imaging techniques to capture the full coacervate trafficking process and maturation, from early endosomes to late endosomes to lysosomes.